Why are Chloris gayana leaves shorter in salt-affected plants? Analyses in the elongation zone - Ortega, Leandro Ismael (2006)
Reduced hydraulic conductance calculated from growth data was suggested to be the main reason for reduced leaf expansion in salt-stressed Chloris gayana (Rhodes grass). In this work, xylem vessel cross-sections and wall enzyme activities were analysed to re-examine the effects of salinity on leaf growth in this species. Maximal segmental growth rates were 20% lower and the growth zone was 23% shorter in leaves from salinized plants than in controls; however, growth rates between 0 mm and 15 mm from the ligule were similar in both types of leaves. Xylem cross-sectional areas in this region were about 65% smaller in leaves of salinized plants, suggesting that hydraulic restrictions in the leaves of salinized plants were much higher than overall growth reductions. Extractable xyloglucan endotransglucosylase activity in this zone was twice as high in leaves of salinized plants as in leaves of controls. Nevertheless, the activity of the extracted enzyme was not affected by up to 1 M NaCl added to the reaction medium. Therefore, increased xyloglucan endotransglucosylase activity under salinity may be due to a promotion of transcription of XTH (xyloglucan endotransglucosylase/hydrolases) genes and/or translation of preformed transcripts. These results suggest that, as in drought stress, increased activity of cell wall enzymes associated with wall loosening may contribute to the maintenance of growth under saline conditions despite hydraulic restrictions.